2014
DOI: 10.1016/j.cie.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Case-Based Reasoning system for mathematical modelling options and resolution methods for production scheduling problems: Case representation, acquisition and retrieval

Abstract: OATAO is an open access repository that collects the work of some Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In terms of SBUCs expressed by a crisp number ( j * ), the similarity SM j * ð Þ XY can be measured by using the Equations ( 2)-(4). For SBUC does not in the format of crisp number (j 0 ), the similarity between the target city and stored cities can be measured by judging whether their conversion values are the same (Ahn et al, 2014;Kocsis et al, 2014;Shen, Yan, Zhang, & Shuai, 2017). For example, conversion value for landform characteristic of hills, plains, mountains, plateaus can be defined as 100, 200, 300, 400.…”
Section: Similarity Measure Of Sbucsmentioning
confidence: 99%
“…In terms of SBUCs expressed by a crisp number ( j * ), the similarity SM j * ð Þ XY can be measured by using the Equations ( 2)-(4). For SBUC does not in the format of crisp number (j 0 ), the similarity between the target city and stored cities can be measured by judging whether their conversion values are the same (Ahn et al, 2014;Kocsis et al, 2014;Shen, Yan, Zhang, & Shuai, 2017). For example, conversion value for landform characteristic of hills, plains, mountains, plateaus can be defined as 100, 200, 300, 400.…”
Section: Similarity Measure Of Sbucsmentioning
confidence: 99%
“…uses solution found in the past for a similar problem in the present [10][11][12][13][14]. Precedent or case base (CB) serves as a knowledge base in CBR-systems, meanwhile reasoning consists of four basic stages, also known as CBR-cycle [13]: Retrieval, Reuse, Revision and Retention.…”
Section: Models and Methodsmentioning
confidence: 99%
“…Firstly, since KCs are key product features that reflect typical properties of a product, they are usually utilized to find the most useful cases to help solve a target problem by calculating the similarity of KCs in available cases. Peng et al [2], Kocsis et al [3], and Zhu et al [4] used KCs as an enabler to select a similar case during an engineering design phase. While Romli et al [5] found the optimal from all possible solutions based on KCs to support sustainable product design.…”
Section: The Application Of Kcsmentioning
confidence: 99%
“…Some enterprises and scholars used a method called key characteristic (KC) control to alleviate the above problems, such as using KCs to capture the most similar instances [2][3][4][5], or using KCs as an efficient medium for communication with suppliers [6,7]. However, at present, there is no mutual definition for a KC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation